Sinergi Tradisi dan Psikologi; Efektivitas Sorogan dan Bandongan dalam Pembelajaran Pesantren - Muhammad Iqbal Rosyid; Rifdatul Aisy; Nurul Mubin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the effectiveness of the sorogan and bandongan methods in Islamic boarding school (pesantren) learning through the perspective of educational psychology. Using a qualitative-descriptive approach based on library research, this study explores the relevance of these traditional teaching methods to behaviorist, cognitivist, and constructivist learning theories. The findings reveal that the sorogan method, which emphasizes personal interaction between students (santri) and teachers (kiai), plays a crucial role in improving reading accuracy, learning discipline, independence, and metacognitive abilities. Meanwhile, the bandongan method, which is conducted collectively, proves effective in strengthening conceptual understanding, fostering social learning, and internalizing moral and spiritual values within a communal context. The integration of these two methods represents a synergy between the intellectual tradition of pesantren and the principles of modern educational psychology that emphasize affective, cognitive, and psychomotor aspects. The results indicate that the combined application of sorogan and bandongan can support the development of an adaptive pesantren curriculum aligned with the demands of 21st-century education while maintaining the Islamic scholarly tradition that serves as the foundation for character formation and personal development.